Civil War Senator : William Pitt Fessenden and the Fight to Save the American Republic - Cook, Robert J., 1958- (Book collections on Project MUSE., 2011)
One of the most talented and influential American politicians of the nineteenth century, William Pitt Fessenden (1806-1869) helped devise Union grand strategy during the Civil War. A native of Maine and son of a fiery New England abolitionist, he served in the United States Senate as a member of the Whig Party during the Kansas-Nebraska crisis and played a formative role in the development of the Republican Party. In this richly textured and fast-paced biography, Robert J. Cook charts Fessenden's rise to power and probes the potent mix of political ambition and republican ideology which impell.